Modifikasi Handy Talky (HT) Sebagai Telealarm Pengaman Benda – Benda Suci Pratima Di Pura Dari Tindakan Pencurian - Gopal, I Made Anand; Rahardjo, Pratolo; Jasa, Lie (Jurnal Teknologi Elektro; Vol 16 No 1 (2017): (January - April) Majalah Ilmiah Teknologi Elektro, 2016)
The Criminal acts of stealing sacred objects Pratima in Bali becoming more frequent, so that the required modern electronic security system that is expected to facilitate the public in improving security the sacred objects which are in the temple area from the thieves. Then needed a safety telealarm of Pratima. The safety telealarm consist of four sensors, namely: a touch sensor, light sensor, dark sensor and IR LED sensor. And also used Handy talky (HT) redell DL-5108 which has been modified as transmitter, which directly connected to the Handy Talky (HT) of the village security officer, so that the safety of sacred objects Pratima can be kept more stringent. Keyword: Telealarm, Pratima, Handy Talky, sensor DOI: 10.24843/MITE.1601.02